Terms of Reference: Review of Culture and Engagement in CGIAR - CGIAR Independent Advisory and Evaluation Service (CGIAR Independent Advisory and Evaluation Service, 2025)
Under the System Council (SC)-endorsed Multi-Year Evaluation Plan (MYEP) (2025-27 Workplan for IAES (SC/M21/DP5)), the review of the 2020-27 Gender, Diversity and Inclusion (GDI) Action Plans and the Action Plan for Advancing Culture and Engagement (C&E) in CGIAR’s Workplaces is a joint activity between the Evaluation Function (EF) and the CGIAR Internal Audit (IA) function. Recommendations will be subject to a CGIAR Management Response (MR). In 2017, Evaluation of the Gender at the CGIAR Workplace was conducted with MR available on evaluation function website and summed up in Annex 4.